ANALISIS PENGARUH ATRIBUT PRODUK, CITRA MEREK DAN PERSEPSI HARGA TERHADAP PROSES KEPUTUSAN PEMBELIAN SEPEDA MOTOR MATIC HONDA VARIO (Studi Pada Konsumen di Kelurahan Rejosari, Semarang Timur ) - Andhika Rusmiani, 14.05.51.0154; Sutedjo, Bambang (Students' Journal of Economic and Management, 2018)
The purpose of this research is to know and analyze the influence of each variable of product attribute, brand image and price perception to decision process of purchasing motorcycle matic Honda Vario. The population in this study is the owner of Honda Vario motor matic in Rejosari Village, East Semarang. The sampling technique in this research uses purposive sampling, because in determining the sample based on certain criteria, namely: people who make decision process of purchasing motorcycles matic Honda Vario, and residing in Rejosari Village, East Semarang and more than 17 years old. The analytical tool used is multiple linear regression analysis.The results of the analysis can be concluded, that: product attributes have no significant effect on the purchasing decision process of Honda Vario matic motorcycle. Brand image has a positive and significant impact on the purchasing decision process of Honda Vario matic motorcycle. Price perceptions have a positive and significant impact on the purchasing decision process of Honda Vario matic motorcycle.Keywords: product attributes, brand image, price perception, and purchasing decision process